Technique for definition of break size of road covering on the bridge - Sužiedelytė-Visockienė, Jūratė (Transport, 2007)
The article deals with the submitted photogrammetric method for image rectification to the planar coordinate system. The images are taken by metric digital camera Canon EOS 350D. The camera is calibrated with Technet(Pictran B, D/E) software using the special test‐field for calibration. Calibration parameters are determined to the images rectification process. The images in the planar coordinate system are transformed to 5 control points with the same software. The received results are visible in tables and figures. The transformed, planar images can be applied to research, designing and deformations estimate of engineering constructions. First Published Online: 27 Oct 2010